2011
DOI: 10.1111/j.1474-919x.2011.01109.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigator disturbance reduces reproductive success in Short‐tailed Shearwaters Puffinus tenuirostris

Abstract: Research procedures can have a detrimental effect on the reproductive success of the study species. In this study, the frequency of investigator disturbance on Short‐tailed Shearwaters Puffinus tenuirostris was examined experimentally throughout the incubation period to assess whether disturbance influences hatching success, pre‐fledging chick survival and chick body size. Handling of incubating birds every day, every 3 days and once a week reduced hatching success by 100, 61 and 39%, respectively, compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…However, it is possible that this reduction in nest predation will negatively affect nest predators. Moreover, research activities could negatively affect the focal species in other subtle ways, such as a change in breeding density or an increase in the level of stress that may result in lower fitness (Carey 2011). Therefore, managers should evaluate carefully their main conservation goals when granting research projects for the areas under their supervision.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that this reduction in nest predation will negatively affect nest predators. Moreover, research activities could negatively affect the focal species in other subtle ways, such as a change in breeding density or an increase in the level of stress that may result in lower fitness (Carey 2011). Therefore, managers should evaluate carefully their main conservation goals when granting research projects for the areas under their supervision.…”
Section: Discussionmentioning
confidence: 99%
“…assigning an incubation strategy, documenting recess activity or monitoring the nest survival) can be achieved by visiting the nest-site only once during incubation, the disturbance by observers and possible related biases can be reduced to a minimum. Indeed, frequent visits to nests may reduce nest attendance by parents and increase the risk of nest abandonment or nest predation (Ellison & Cleary 1978, Lenington 1979, Westmoreland & Best 1985, Major 1990, Gotmark 1992, Verboven et al 2001, Weidinger 2006, Carey 2011, but see also Ibañez-Alamo et al 2012). This concern is important in the Arctic where many nests are depredated by Arctic Foxes Vulpes lagopus (Reneerkens et al 2016), which have an excellent sense of smell (Kolenosky 1987, Lai et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, frequent visits to the nest necessarily induce some anthropogenic impacts and can hence bias other parameters under study. Indeed, previous studies showed that the presence of an observer might alter the behaviour of birds (Weidinger 2006, Carey 2011, can reduce nest attendance by parents (Verboven et al 2001), and increase the likelihood of nest abandonment (G€ otmark 1992) or nest predation (Major 1990). This is particularly the case for studies of species with little or no sexual dimorphism, requiring researchers to catch and mark individually at least one of the incubating adults to identify whether one or two adults are incubating a clutch.…”
mentioning
confidence: 99%
“…Indeed, most of the time, the impact of investigators is seen from the disturbance effect point of view either on breeding success (Bolduc and Guillemette 2003, Blackmer et al 2004, Ibáñez-Álamo et al 2012, growth of chicks (Sandvik and Barrett 2001, O'Dwyer et al 2006, Carey 2009, 2011, or on behaviour and physiology (van Oers and Carere 2007) but rarely, to our knowledge, considering the identity of the people in charge of the experiment on wildlife fauna (see, however, Slobodchikoff et al 1991, Levey et al 2009, Marzluff et al 2010, Lee et al 2011, Davidson et al 2015. Indeed, most of the time, the impact of investigators is seen from the disturbance effect point of view either on breeding success (Bolduc and Guillemette 2003, Blackmer et al 2004, Ibáñez-Álamo et al 2012, growth of chicks (Sandvik and Barrett 2001, O'Dwyer et al 2006, Carey 2009, 2011, or on behaviour and physiology (van Oers and Carere 2007) but rarely, to our knowledge, considering the identity of the people in charge of the experiment on wildlife fauna (see, however, Slobodchikoff et al 1991, Levey et al 2009, Marzluff et al 2010, Lee et al 2011, Davidson et al 2015.…”
Section: Methodological Caveatsmentioning
confidence: 99%